-17/6 13,17,-13,9,-18
Пошаговое объяснение:
6х+17=0
6х+17-17=0-17
6х=-17
6х/6=-17/6
12х+47 =13 ,17 ,9,-13,-18
12х+47=13 12х+47=-13 12х+47=-18
х=12×5=60 х=12×(-5)=-60 х=12х+47-47=-18-47
х=60-47 х = -60+47 12х=-65
х=13 х=-13 12х/12=-65/12
х= -65/12
12х+47=9 12х+47=17
12х+47-47=9-47 12х+47-47 =17-47
12х=-38 12х=-30
12х/12=-38/12 12х/12=-30/12
-19/6 -5/2
-17/6 13,17,-13,9,-18
Пошаговое объяснение:
6х+17=0
6х+17-17=0-17
6х=-17
6х/6=-17/6
12х+47 =13 ,17 ,9,-13,-18
12х+47=13 12х+47=-13 12х+47=-18
х=12×5=60 х=12×(-5)=-60 х=12х+47-47=-18-47
х=60-47 х = -60+47 12х=-65
х=13 х=-13 12х/12=-65/12
х= -65/12
12х+47=9 12х+47=17
12х+47-47=9-47 12х+47-47 =17-47
12х=-38 12х=-30
12х/12=-38/12 12х/12=-30/12
-19/6 -5/2